Capital Structure And Cost Of Capital: A Case Of Malaysia - Asl, Hossein Javadi (2008)
The purpose of this study is to estimate the cost of capital to a sample of listed companies in Kuala Lumpur stock Exchange (KLSE) Main Board, drawn form the industrial sector for the years 2005 and 2006.